Vagal nerve stimulation dynamically alters anxiety-like behavior in rats - A.G. Butler; J.K. Bassi; A.A. Connelly; M.R. Melo; A.M. Allen; S.J. McDougall (Brain Stimulation)
Background: Electrical vagal nerve stimulation (VNS), at currents designed to target sensory, interoceptive neurons, decreases anxiety-like behavior. Objective/Hypothesis: We hypothesized that different VNS current intensities would differentially alter anxiety-like behavior through the activation of distinct brainstem circuits. Methods: Electrodes were implanted to stimulate the left vagus nerve and to record diaphragm muscle and electrocardiogram activity. The VNS current required to elicit the A-fiber-mediated Hering-Breuer Reflex (HBR) was determined for each animal. Based on this threshold, animals received either sham stimulation or VNS at 1.5 (mid-intensity VNS) or 3 (higher-intensity VNS) times the threshold for HBR activation. Anxiety-like behavior was assessed using the elevated plus maze, open field test, and novelty-suppressed feeding test. Additionally, a place preference assay determined whether VNS is rewarding or aversive. Finally, a c-Fos assay was performed to evaluate VNS-driven neuronal activation within the brainstem. Results: Mid-intensity VNS reduced anxiety-like behavior in the elevated plus maze and open field test. Higher-intensity VNS was aversive during the place preference assay, confounding anxiety measures. Both intensities increased overall c-Fos expression in neurons within the nucleus of the solitary tract, but mid-intensity VNS specifically increased c-Fos expression in noradrenergic neurons within the nucleus of the solitary tract while decreasing it in the locus coeruleus. In contrast, higher-intensity VNS had no effect on c-Fos expression in noradrenergic neurons of either the nucleus of the solitary tract or locus coeruleus. Conclusion: Delivery of VNS induced reproducible, current intensity-dependent, effects on anxiety-like and aversive behavior in rats.